Peningkatan Kesadaran Menabung Sejak Usia Dini Melalui Media Celengan Kreatif di SDN 15 Nusa Indah Kota Bengkulu - Tista, Jesica Dara; Rahmawati, Jesicca Ayu; Viola, Grache; Rifa’i, Rifa’i (Annusfy : Journal of Multidisciplinary Research, 2025)
The habit of saving from an early age is an important foundation for building financial literacy. This community service program aims to instill an understanding of saving through a creative approach at SD Negeri 15 Nusa Indah, Bengkulu City. The method used combines the presentation of the concept of saving with the practice of recycling used bottles into functional piggy banks. The activity took place in a series of interactive sessions involving the active participation of all students. Evaluation results showed an increase in the understanding of the concept of saving and participants' enthusiasm for managing their personal finances. This project-based learning approach is proven to be effective not only instilling the habit of saving but also fostering creativity and environmental awareness. This program has successfully created a sustainable impact in developing a thrifty and financially savvy character in students.